Validation of Calochortus ownbeyi (Liliaceae), a new species from northwestern Mexico - García-Martínez, Miguel A.; Rodríguez, Aarón; Mcdonald, Hugh P. (Phytotaxa, 2017)
The name Calochortus ownbeyi has been extensively used even though it was not validly published. Accordingly, we are here validating and illustrating this species. Calochortus ownbeyi can be confused with C. venustulus, but there is morphological and molecular evidence that they are distinct species. A comparison between these two taxa and a distribution map are provided.